Chemical constituents of marine-derived cctinomycete Streptomyces fradiae G650 - Hue, Nguyen Thi; Linh, Nguyen Thuy; Minh, Le Thi Hong; Huyen, Vu Thi Thu; Huong, Doan Thi Mai; Cuong, Pham Van (Vietnam Journal of Science and Technology, 2022)
In our continuing search for bioactive molecules, we collected a Streptomyces fradiae strain cultured from a prickly pen shell sample obtained at Van Phong, Khanh Hoa province, Vietnam. The ethyl acetate extract of Streptomyces fradiae G650 exhibited the strong inhibition against a panel of gram-positive bacteria including Enterococcus faecalis ATCC 29212, Staphylococcus aurerus ATCC 25923, Bacillus cereus ATCC 14579, and the yeast Candida albicans with the MIC values of 8, 32, 32, 8 µg/mL, respectively. As a result, from the marine-derived actinomycete Streptomyces fradiae G650, six compounds were isolated, including15α-hydroxyneoline (1), cyclo-(Leu-Tyr) (2), cyclo-(Pro-Gly) (3), 2'-deoxyuridine (4), uridine (5), and adenine (6). These compounds were structurally characterized via 1D and 2D NMR spectroscopic, mass spectrometric analyses and by comparison of the spectral data with those of previously reported data. To the best of our knowledge, 15α-hydroxyneoline (1) was reported to be isolated from microorganism for the first time.